Persepsi Anak terhadap Peran Ayah dalam Keluarga dan Implikasinya terhadap Pelayanan Bimbingan dan Konseling - M David; Daharnis Daharnis; Azrul Said (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Dad has a special role to the child. Fathers who work casually have a limited time to be with his children. The purpose of this research is to know the child's perception of the father's role in the family and its implications for guidance and counseling services. This research is descriptive quantitative research with the populations is adolescent. Determination of the number of samples using cluster sampling technique. Retrieval of data using questionnaires and analysis with techniques percentage. The results of this study reveal the child's overall perception of the father's role in the category very well.